School meals and quality of household food acquisitions. Issue 4 (7th January 2021) - Cleary, Rebecca; Bonanno, Alessandro; Ghazaryan, Armen; Bellows, Laura; McCloskey, Morgan
Abstract: School meals provide nourishment to a large portion of US schoolchildren. Research has examined the relationship between the consumption of school meals and the quality of schoolchildren's diets, with little emphasis on studying spillovers at the household level. Using National Food Acquisition and Purchase Survey data and unconditional quantile regression, we study the relationship between a household's quality of food‐at‐home acquisitions and the number of school meals acquired, subsampling households by their Supplemental Nutrition Assistance Program participation status. We do not find strong evidence supporting beneficial spillovers of school meals on a household's quality of food‐at‐home acquisitions. JEL CLASSIFICATION: C31; D12; I14; Q18 Abstract : Related Content: Did the New School Meal Standards Improve the Overall Quality of Children's Diets? Related Content: Are College Students More Likely to Be Food Insecure than Nonstudents of Similar Ages? Related Content: Did State-Mandated Restrictions on Sugar-Sweetened Drinks in California High Schools Increase Soda Purchases in School Neighborhoods?